Factors Influencing The Nutritional Status Of Infants Aged 0-6 Months In Trenggalek - Fajriah, Asruria Sani; Pangestuti, Dymalikhul; Fazrin, Intan; Wulandari, Anggrawati (Journal of Health Science Community, 2025)
Based on an initial survey in February 2022 in the Panggul Health Center work area, there were 365 babies aged 0-6 months, of which 6 babies (1.64%) were obese, 27 babies (7.4%) had overweight, 13 babies (3.56%) had underweight, and 319 babies (87.4%) had normal nutritional status. The purpose of this study was to determine what factors influence the nutritional status of babies aged 0-6 months in the Panggul Health Center work area. This research is an analytical survey research.cross sectional. Respondents were taken using the techniquepurposive sampling. With a sample of 83 people. Independent variables are Gender and Birth Weight of Babies. Dependent variable is Nutritional Status of Babies Aged 0-6 Months. Results: The results of the study showed that most of the babies who had poor nutritional status were male babies, namely 78.6%, and most of the babies had low birth weight, namely 71.43%. The results of the analysis using the chi square test showed that there was a relationship between the sex of the baby and the nutritional status of the baby in the working area of the Pangkal Pinang Health Center.p-valueof 0.001 < 0.05. There is a relationship between the birth weight of babies and the nutritional status of babies in the working area of the Pangkal Pinang Health Center.p-valueof 0.000 < 0.05. Based on the research results, it is known that the variables related to Nutritional Status in Infants Aged 0-6 Months are Gender and Birth Weight of the Infant.